2018
DOI: 10.1186/s12890-018-0633-5
|View full text |Cite
|
Sign up to set email alerts
|

Patient information, education and self-management in bronchiectasis: facilitating improvements to optimise health outcomes

Abstract: BackgroundBronchiectasis is an incurable lung disease characterised by irreversible airway dilatation. It causes symptoms including chronic productive cough, dyspnoea, and recurrent respiratory infections often requiring hospital admission. Fatigue and reductions in quality of life are also reported in bronchiectasis. Patients often require multi-modal treatments that can be burdensome, leading to issues with adherence. In this article we review the provision of, and requirement for, education and information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 87 publications
1
18
0
1
Order By: Relevance
“…These studies, both from the UK, were unable to establish benefits on their primary outcome of health-related quality of life and did not report on some clinically-relevant outcomes like exacerbations requiring antibiotics 16 . On the other hand, qualitative research suggests that information deficits may be a barrier to effective self-management of bronchiectasis 17 . Both knowledge, defined as ‘awareness of the existence of something’, and skills, defined as ‘ability or proficiency acquired through practice’ 18 , are critical capabilities for self-management.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies, both from the UK, were unable to establish benefits on their primary outcome of health-related quality of life and did not report on some clinically-relevant outcomes like exacerbations requiring antibiotics 16 . On the other hand, qualitative research suggests that information deficits may be a barrier to effective self-management of bronchiectasis 17 . Both knowledge, defined as ‘awareness of the existence of something’, and skills, defined as ‘ability or proficiency acquired through practice’ 18 , are critical capabilities for self-management.…”
Section: Introductionmentioning
confidence: 99%
“…Four generic self-management-related assessments were identified: the Patient Activation Measure 20 , the Chronic Disease Self-Efficacy Scale 21 , the Test of Functional Health Literacy in Adults 22 and the Health Education Impact Questionnaire 23 . Aside from being unable to address the specific information needs of patients with bronchiectasis as identified by Hester et al (2018), they also assessed concepts other than self-management knowledge and skills (namely, patient activation and self-efficacy) 17 . Two respiratory-specific assessments were identified.…”
Section: Introductionmentioning
confidence: 99%
“…There are few studies on patient’s education needs in lung diseases. The majority of the available resources are directed at common respiratory diseases, such as chronic obstructive pulmonary disease (COPD) [ 45 ]. Most literature about educational needs in rare lung diseases focused on ILD, especially IPF [ 45 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…The aim is to break the vicious recurrent cycle of infection, inflammation, impaired mucociliary clearance and structural lung damage. In addition to these interventions, treatment-seeking behaviour plans [18] and an educational component are pivotal to facilitate patients with an understanding of the basic principles of disease management and recognition of an exacerbation to enable timely intervention [19]. It is imperative therefore to investigate the efficacy and utility of self-management for patients with bronchiectasis; a research recommendation identified by the European Multicentre Bronchiectasis Audit and Research Collaboration (EMBARC) [20], the Association of Respiratory Nurse Specialists UK [21], and the BTS [1].…”
Section: Introductionmentioning
confidence: 99%